(untitled) (Cambridge [England],New York, 1990)
'Abbasid literature was characterized by the emergence of many new genres and of a scholarly and sophisticated critical consciousness. This volume of The Cambridge History of Arabic Literature covers the prose and poetry produced in the heartland and provinces of the 'Abbasid Empire from the mid-eighth to the thirteenth centuries A.D. Chronologically organized, the book explores the main genres and provides extended studies of major poets, prose writers and literary theorists. To make the material accessible to nonspecialist readers, 'Abbasid authors are quoted in English translation wherever possible, and clear explanations of their literary techniques and conventions are provided. The volume concludes with the first comprehensive survey of the relatively unknown literature of the Yemen to appear in a European language since the manuscript discoveries of recent years.
Keywords: Arabic literature,Văn học A Rập; History and criticism,Lịch sử và phê bình; 750-1258,750-1258